Gerak Migrasi Penduduk Pesisir Implikasinya terhadap Ekonomi Kependudukan - Akhmad Firman; Mustakim Mustakim (Universitas Musamus, Merauke, Papua, 2020)
The problem of migration has always been a big problem faced by the current population. To get out ofthe poverty zone, the movement trend of migration becomes the gateway in solving the problem ofeconomic inequality. This research study is about the phenomenon of migration in Buton coastalcommunities. The purpose of this study was to understand the migration patterns of the coastal populationof Buton. This study uses a qualitative method with a descriptive approach with the analysis processconsisting of data reduction, data preservation and data verification, which in turn draws conclusionsfrom the research results. The results showed that the movement of migration was caused by the pushpullfactor where the driving factor was the reason for leaving the area of origin while the pull factorwas the reason for choosing the destination area. In the analysis of the motive motive for migration ofthe coastal population of Buton, it is indicated by a seasonal factor which in turn becomes a drivingfactor for the coastal community of Buton Regency to move to work as clove laborers where from thesejobs they can earn tens of millions of rupiah per season. The author argues that the movement ofattraction and driving force is the main factor in the migration of coastal populations.